Coping humor for the relationship between a sense of stress at work and job satisfaction - Agnieszka Kruczek; Małgorzata Anna Basińska (Nofer Institute of Occupational Medicine, 2018)
Background Humor is considered as a personal resource that allows individuals to effectively deal with stressful situations at work by reducing tension and perceiving the situation as less threatening. By reducing stress, humor contributes to increased job satisfaction. Material and Methods A total of 201 professionally active participants (113 women and 88 men) aged 19-60 years old were qualified for the study - the average age in the study group was 37.76 years (SD = 12.04). The study was conducted for 1 month (at the turn of February and March 2017). The following methods were used in the research: Coping Humor Scale (CHS), Satisfaction with Job Scale (SSP), Sense of Stress at Work Scale (PSS-10-P) and own survey. Results Humor coping with stress partially mediates the relationship between a sense of stress at work and job satisfaction. It is associated with less tension at work and greater job satisfaction. Conclusions Coping humor with stress increases the individual adaptation capacity in the face of stress at work, by shifting the perspective, distancing from problems at work and changing stressors appraisal as less threatening. Med Pr 2018;69(6):621-631